Mind-mapping for conceptual material of introduction to management - Rr. Sri Kartikowati; Gimin Gimin; Sakdanur Sakdanur (Universitas Riau, 2018)
Students with difficulty in comprehending conceptual materials need media that has powers in organizational, procedural visual, and supporting creative thinking; all are integrated in a mind-mapping media. This research is aimed to develop a learning design of Introduction to Management based on mind-mapping media concerning with conceptual materials. This is an early phase of research and development activities, in Introduction to Management class. Data of needs analysis is obtained through survey technique on 38 college students, then followed by literature study and focus group discussions. The result shows that a learning design of Introduction to Management, that highlights conceptual materials, has constructed on the basis of mind-mapping media. The design consisted of learning outcome, stages of preparing mind mapping media, and measurement method of effectiveness of the learning design implementation.